Optoelectronic analysis of silicon doped ZnGa2S4: A first principle study. (December 2020) - Gaur, A; Khan, K; Soni, A; Dashora, A; Sahariya, J; Ahuja, U
Abstract: This paper depicts a comprehensive investigation of Si doping on the wide bandgap ternary semiconductor ZnGa2 S4 . The first principles Wien2k code is utilized by adopting the Perdew-Burkhe-Ernzerhof Generalized Gradient Approximation (PBE-GGA) method. Band engineering is done in order to get a suitable value of bandgap in the region of solar spectrum. For this purpose the doping of Si and its effect on ZnGa2 S4 is investigated. The bandgap computed by the doping of Si atom has turned out to be 2.14 eV which has decreased in comparison to the bulk compound 2.38 eV. Electronic and optical properties of this doped material are studied. The integrated absorption curve offers a value of 61.205. The imaginary part of the dielectric tensor offers peaks which help in understanding the inter-band transitions. Also the values of reflection and refractive index are calculated exploring the feature of optical properties in the wien2k package.